Transformed notochordal cells trigger chronic wounds in zebrafish, destabilizing the vertebral column and bone homeostasis - Paco López-Cuevas; Luke Deane; Yushi Yang; Chrissy L. Hammond; Erika Kague (The Company of Biologists, 2021)
Notochordal cells play a pivotal role in vertebral column patterning, contributing to the formation of the inner architecture of intervertebral discs (IVDs). Their disappearance during development has been associated with reduced repair capacity and IVD degeneration. Notochord cells can give rise to chordomas, a highly invasive bone cancer associated with late diagnosis. Understanding the impact of neoplastic cells during development and on the surrounding vertebral column could open avenues for earlier intervention and therapeutics. We investigated the impact of transformed notochord cells in the zebrafish skeleton using a line expressing RAS in the notochord under the control of the kita promoter, with the advantage of adulthood endurance. Transformed cells caused damage in the notochord and destabilised the sheath layer, triggering a wound repair mechanism, with enrolment of sheath cells (col9a2+) and expression of wt1b, similar to induced notochord wounds. Moreover, increased recruitment of neutrophils and macrophages, displaying abnormal behaviour in proximity to the notochord sheath and transformed cells, supported parallels between chordomas, wound and inflammation. Cancerous notochordal cells interfere with differentiation of sheath cells to form chordacentra domains, leading to fusions and vertebral clefts during development. Adults displayed IVD irregularities reminiscent of degeneration, including reduced bone mineral density and increased osteoclast activity, along with disorganised osteoblasts and collagen, indicating impaired bone homeostasis. By depleting inflammatory cells, we abrogated chordoma development and rescued the skeletal features of the vertebral column. Therefore, we showed that transformed notochord cells alter the skeleton during life, causing a wound-like phenotype and activating chronic wound response, suggesting parallels between chordoma, wound, IVD degeneration and inflammation, highlighting inflammation as a promising target for future therapeutics. This article has an associated First Person interview with the first author of the paper.